2013
DOI: 10.1186/ar4408
|View full text |Cite
|
Sign up to set email alerts
|

The cytokine and chemokine expression profile of nucleus pulposus cells: implications for degeneration and regeneration of the intervertebral disc

Abstract: IntroductionThe aims of these studies were to identify the cytokine and chemokine expression profile of nucleus pulposus (NP) cells and to determine the relationships between NP cell cytokine and chemokine production and the characteristic tissue changes seen during intervertebral disc (IVD) degeneration.MethodsReal-time q-PCR cDNA Low Density Array (LDA) was used to investigate the expression of 91 cytokine and chemokine associated genes in NP cells from degenerate human IVDs. Further real-time q-PCR was used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
94
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(102 citation statements)
references
References 51 publications
1
94
1
Order By: Relevance
“…It was shown that several cytokines are locally increased in IVD diseases [17] and MSCs were suggested to be implicated in their production [8,18]. In cells isolated from human D-IVDs and H-IVDs, we observed an extensive cytokine and chemokine expression profile, reinforcing the potential of these factors to act as intercellular signaling molecules under pathological conditions.…”
Section: Discussionmentioning
confidence: 54%
“…It was shown that several cytokines are locally increased in IVD diseases [17] and MSCs were suggested to be implicated in their production [8,18]. In cells isolated from human D-IVDs and H-IVDs, we observed an extensive cytokine and chemokine expression profile, reinforcing the potential of these factors to act as intercellular signaling molecules under pathological conditions.…”
Section: Discussionmentioning
confidence: 54%
“…A strong difference was observed in the levels of nerve growth factor (NGF), neurofilament-68, growth-associated protein (GAP)-43, and substance P in invading nerve fibers, in and around the outer layer of uncontained herniated versus spondylotic IVDs [116]. Another study that evaluated 91 cytokine-and chemokine-associated genes in human NP cells showed that NP cells are a source of IL-16, CCL2, CCL7 and CXCL8 [88]. Some of the pro-inflammatory cytokines usually present at increased levels in human degenerated discs, such as IL-1b and TNF-a, may mediate catabolic effects, decreasing proteoglycan production and enhancing MMP expression [71,111,134,135].…”
Section: Degenerated Samplesmentioning
confidence: 99%
“…Furthermore, a recent robust analysis of cytokine/chemokine expression profile of human NP cells has presented clear evidence that NP cells, or at least some of them, are producers of specific inflammation-associated molecules, even in basal conditions (non-degenerated NP) [88]. In addition, infiltrated leukocytes (CD11b-positive cells) were found even in prolapsed IVDs, where NP is supposedly intact and isolated from any vascular source of immune cells [88]. The question of whether these cells could be resident macrophages or macrophage-like cells remains.…”
Section: Mmp19mentioning
confidence: 99%
“…The expression and release of CCL5/RANTES is further correlated with the proinflammatory mediators IL-1 and TNF-α, which are known to be up-regulated in degenerative discs [123][124][125][126]. In a similar study, specifically looking at the cytokine and chemokine expression in the nucleus pulposus, the chemokines CCL2, CCL7 and CXCL8 were found to be increased in degenerative disc specimens [127]. Moreover, up-regulation of the chemokine CCL3 was observed in NP cells after exposure to the pro-inflammatory mediators IL-1 and TNF-α [128].…”
Section: Accepted Manuscriptmentioning
confidence: 74%